The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2527/jas.2016-0561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on the fundamental color chemistry of dark-cutting beef

Abstract: The objective of the current study was to evaluate the effects of aging on myoglobin chemistry of dark-cutting beef. Ten USDA Choice (mean pH = 5.6; normal pH beef) and 10 no-roll dark cutter (mean pH = 6.4) strip loins were obtained from a commercial packing plant within 3 d of harvest. Loins were cut into 4 sections, vacuum packaged, randomly assigned to 0-, 21-, 42-, and 62-d aging at 2°C in the dark. Following aging, loin sections were cut into 2.5-cm-thick steaks and were used to determine bloom developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 31 publications
5
44
0
1
Order By: Relevance
“…Previous research from our laboratory has indicated that blooming properties of dark-cutting steaks were improved with extended aging (English et al, 2016a). Greater myoglobin oxygenation, in part, can be due to decreased mitochondrial activity.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous research from our laboratory has indicated that blooming properties of dark-cutting steaks were improved with extended aging (English et al, 2016a). Greater myoglobin oxygenation, in part, can be due to decreased mitochondrial activity.…”
Section: Discussionmentioning
confidence: 88%
“…Dark-cutting beef has more myoglobin concentration than normal-pH beef (McKeith et al, 2016;English et al, 2016a). With a greater myoglobin concentration, one can speculate a bright-red color for dark-cutting steaks in CO-MAP than normal-pH steaks in CO-MAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Color stability studies in pH > 5.8 muscles are published mostly from Bos taurus beef (ABRIL et al, 2001;ENGLISH et al, 2016;MCKEITH et al, 2016). There is a lack of researches investigating Nellore beef with increased pHu.…”
Section: Introductionmentioning
confidence: 99%